2014
DOI: 10.5869/fc.2014.v20-1.61
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of extreme events on southeastern Australian freshwater crayfish

Abstract: Extreme events like wildfire, flooding and drought, and activities related to managing these events (fire dam, bridge and road construction and water regulation) potentially impact freshwater crayfish populations, although limited information exists. Our study analysed abundance data for four freshwater crayfish species across an 11-year period, including pre-and post-wildfire and post-flooding data, and describes the impacts of human actions on their populations in the Grampians National Park in Victoria, Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, in this study, the decreased abundance during the subsequent hydroperiod of organisms that aestivate in sediment may indicate direct burning or the effects of radiant heat on these animals while resting in the sediment during the dry periods (Cowell, Matthews, & Lind, 2006). Decreased abundances of specific groups after wildfire due to direct burning have been recorded for zooplankton in rice paddies and crayfish in streams and temporary wetlands (Chittapun, 2011;Johnston, Matthews, Robson, & Chester, 2014). Although other studies with less intense controlled burns detected no direct effect of fire on anostracan cysts (Wells, Hathaway, & Simovich, 1997).…”
Section: Community Composition and Functional Traitsmentioning
confidence: 61%
See 1 more Smart Citation
“…However, in this study, the decreased abundance during the subsequent hydroperiod of organisms that aestivate in sediment may indicate direct burning or the effects of radiant heat on these animals while resting in the sediment during the dry periods (Cowell, Matthews, & Lind, 2006). Decreased abundances of specific groups after wildfire due to direct burning have been recorded for zooplankton in rice paddies and crayfish in streams and temporary wetlands (Chittapun, 2011;Johnston, Matthews, Robson, & Chester, 2014). Although other studies with less intense controlled burns detected no direct effect of fire on anostracan cysts (Wells, Hathaway, & Simovich, 1997).…”
Section: Community Composition and Functional Traitsmentioning
confidence: 61%
“…While the taxonomic approach did not detect wildfire impacts, the functional approach detected stronger consequences of wildfire on all functional groups. Decreased abundances of specific groups after wildfire due to direct burning have been recorded for zooplankton in rice paddies and crayfish in streams and temporary wetlands (Chittapun, 2011;Johnston, Matthews, Robson, & Chester, 2014). Direct impacts of fire such as mortality (Gresswell, 1999) are commonly found in stream fishes and are associated with an increase in water temperatures or ammonia intoxication due to smoke diffusion (Beakes, Moore, Hayes, & Sogard, 2014;Isaak et al, 2010).…”
Section: Community Composition and Functional Traitsmentioning
confidence: 99%
“…Likewise, species differ in their capacity to recover from population loss due to differences in habitat and resource specificity, fecundity, and dispersal capacity. Although there is some evidence from previous studies of impacts of fire (e.g., Fox, 1982;Friend, 1993;Johnston et al, 2014;Lindenmayer et al, 2021;Loyn, 1997;Lyon & O'Connor, 2008;Westgate et al, 2018) there is limited or no information on the fire responses of most species, especially in relation to fires of the scale and severity of the 2019-2020 Australian megafires (Jolly, Dickman, et al, 2022;Pausas & Parr, 2018;Rowley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ectothermic species tolerate thermal increases up to an upper limit, defined as the critical thermal maximum, after which further increases in temperature are lethal (Pörtner & Peck, 2010). Although the localized mortality of aquatic organisms is often reported following major wildfire events (Burton, 2005;Driessen, 2019;Johnston et al, 2014;Silva et al, 2020), this review found no evidence of direct mortality of aquatic fauna attributable to extreme water temperatures caused by wildfires. However, periods of warming during and after a fire could result in local extirpation of species if species-specific thermal limits are surpassed.…”
Section: Water Temperaturementioning
confidence: 80%